Diseño de un tablero de control que permita monitorear la ejecución de los proyectos de inversión financiados con recursos de sistema general de regalías (2017)
Information Technologies play a relevant role as they let us gather, persist and process the data that is generated from business that support the enterprise operation. Business Intelligence is define as the combination of technology, tools and processes that may transform data into information, then into knowledge and this one taken into a define strategy that support decision making based on precise, accurate and reliable information to solve many kind of situations present on operations. This document is the design of a Dashboard for projects founded with royalties monitoring, providing key indicators to mesure the performance and management of the projects executors on the use of this royalties economic resources.